Identifikasi dan Distribusi Gulma di Lahan Pasir Pantai Samas, Kabupaten Bantul, Daerah Istimewa Yogyakarta - Junaidi Ilham (Universitas Muhammadiyah Yogyakarta, 2014)
A research on identification and distribution of weed on samas coastal, Bantul, DIY aims to get the types and distribution of weeds in the area of Samas sandy coastal, in recognition of the types and characteristics of weeds in fields Samas beach sand to ease in weed control. The research was conducted by survey method that the implementation techniques used the analysis of vegetation and interviews. Vegetation analysis to determine the dominant plant species, determine sample plots observation and further to identify weeds, observed variables in the identification of weeds is weed density, frequency of weeds, weed dominance, coefficient of community (C) and SDR (summed Dominance Ratio). Data from the analytic vegetation result in the form of quantitative data were further analyzed using analysis of variance. Interviews were conducted to obtain information about weed control that usually done by farmers in Samas beach sand land. The results of research showed that weeds dominant in each plant peppers, eggplant, corn and peanuts and dominant weeds on Samas sandy coastal is narrow- leaved weeds, including weeds class C4, that is Eleusine indica L, Cyperus rotundus, Digitaria ciliaris and Cyperus iria effectively controlled by means of preventive, technical culture, mechanical and biological.